SYNTHESIS AND STRUCTURAL CHARACTERIZATION OF UNDOPED CEO2 AND PD DOPED CEO2 FOR PHOTO CATALYTIC STUDIES UNDER SUNLIGHT AND UV-LIGHT IRRADIATION. - M. Mylarappa, G.O. Obaiah, K.H. Shivaprasad (International Journal of Advanced Science and Technology, 2020)
The main objective of the analysis is concentrated on the preparation and fabrication of doped and undoped CeO2 nanoparticles by solution combustion technique to taken glycine as fuel. The correct size and morphology of the doped metal compounds were studied Scanning microscope (SEM). The composition of ceria (CeO2) and palladium substituted Ceria (Ce0.98Pd0.02O2) was confirmed from the powder X-ray Diffractometer (PXRD). The functional groups were analyzed by Fourier transfer infrared spectroscopic analysis, XRD, RR, UV–Vis, and XPS. Photocatalytic properties of CeO2 and palladium doped CeO2 (Ce0.98Pd0.02O2) nanoparticles (NPs) were studied using the radiation conjugation of red (CR) under UV light and sunlight exposure. Based on the XRD analysis, CeO2 and Pd doped CeO2 NPs were formed as crystal structures. CeO2 and Pd doped CeO2 showed excellent Photocatalytic activity by degrading more than 92% of the CR color in the intervals of 120 min under UV light and sunlight.